Peran Hedonic Shopping Motivation Sebagai Mediasi pada Pengaruh Review Influencer dan Islamic Lifestyle Terhadap Perilaku Impulsive Buying - Dea Andani Nur’aini (Intitut Agama Islam Nasional Laa Roiba Bogor, 2026)
This study aims to analyze the influence of Influencer Reviews and Islamic Lifestyle on Impulsive Buying behavior, with Hedonic Shopping Motivation as a mediating variable. This study used a quantitative approach with primary data obtained through an online questionnaire. The sampling technique used was purposive sampling, with 206 respondents. Data analysis was conducted using Partial Least Squares Structural Equation Modeling (PLS-SEM) with the SmartPLS application version 4.0. The results of the study indicate that Influencer Reviews and Islamic Lifestyle significantly influence Impulsive Buying. Furthermore, Influencer Reviews and Islamic Lifestyle also significantly influence Hedonic Shopping Motivation. Furthermore, Hedonic Shopping Motivation is proven to have a significant effect on Impulsive Buying and is able to mediate the influence of Influencer Reviews and Islamic Lifestyle on Impulsive Buying.